Pompe disease in China: clinical and molecular characteristics - Li, Jing; Shi, Xiaohe; Wang, Bo; Hsi, David H.; Zhu, Xiaoli; Ta, Shengjun; Wang, Jing; Lei, Changhui; Hu, Rui; Huang, Junzhe; Zhao, Xueli; Liu, Liwen (Frontiers in Cardiovascular Medicine, 2023)
Background: Pompe disease (PD) is a rare, progressive, and autosomal recessive lysosomal storage disorder caused by mutations in the acid α-glucosidase gene. The clinical course and molecular mechanism of this disease in China have not been well defined.Methods: In this single-center cohort study, we investigated a total of 15 Chinese patients with Pompe disease to better understand the clinical manifestations, echocardiographic imaging and genetic characteristics in this population.Results: The median age of 15 patients at symptom onset was 5.07 months (1-24 months). The median age at diagnosis was 19.53 months (range: 3 to 109 months, n=15). Average diagnostic delay was 13.46 months. None of the patients had received enzyme replacement therapy (ERT). Fifteen patients died at a median age of 24.80 months due to cardiorespiratory failure (range 3-120 months).Myasthenia symptoms and severe hypertrophic cardiomyopathy were universally present (15/15=100%). Global longitudinal strain (GLS) by echocardiography was significantly lower in these patients. After adjusting for gender, body surface area (BSA), left ventricular ejection fraction (LVEF), E/e'ratio, maximum left ventricular wall thickness (MLVWT), left ventricular posterior wall (LVPW), left ventricular outflow tract (LVOT)gradient, GLS was independently correlated with survival time (hazard ratio (HR) = 0.702, 95% confidence Interval (CI): 0.532-0.925, P = 0.012). In2 This is a provisional file, not the final typeset article our cohort, we identified 4 novel GAA mutation: c.2102T>C (p.L701P), c.2006C>T (p.P669L), c.766T>A (p.Y256N), c.2405G>T (p.G802V). 12 patients were compound heterozygotes, and 4 homozygotes.Conclusions: Our study provides a comprehensive examination of PD clinical course and mutations of the GAA gene for patients in China. We showed clinical utility of echocardiography in quantifying heart involvement in patients with suspected PD. GLS can provide prognostic information for mortality prediction. We reported four novel mutations in the GAA gene for the first time. Our findings may improve early recognition of PD characteristics in Chinese patients.